Metal‐Organic Chemical Vapor Deposition of Aluminum Scandium Nitride. Issue 1 (7th November 2019) - Leone, Stefano; Ligl, Jana; Manz, Christian; Kirste, Lutz; Fuchs, Theodor; Menner, Hanspeter; Prescher, Mario; Wiegert, Joachim; Žukauskaitė, Agnė; Quay, Ruediger; Ambacher, Oliver
Abstract : Alloys of scandium with AlN exhibit an enhanced piezoelectric coefficient that can boost the performance of nitride‐based electronic and optoelectronic devices such as high electron mobility transistors (HEMTs). Consequently, there is increasing interest in the epitaxial growth of high‐quality AlScN/GaN heterostructures. So far, only very recent reports on AlScN HEMT structures grown by molecular beam epitaxy (MBE) have been published. Herein, the motivation for depositing AlScN epitaxial layers by metal‐organic chemical vapor deposition (MOCVD) as well as the challenges associated with this approach are explained. For the first time, the successful deposition of epitaxial layers with a Sc content up to 30% (Al0.7 Sc0.3 N) is reported. It is shown that the deposited films consist of wurtzite‐type AlScN with high crystalline quality, demonstrating that MOCVD is suitable for the growth of HEMT structures with Sc‐based ternary nitrides. Abstract : AlScN epitaxial layers with up to 30% Sc concentration are successfully deposited by metal‐organic chemical vapor deposition (MOCVD) onto GaN/Al2 O3 for the first time. A special modification of the MOCVD reactor, needed to promote the incorporation of such high Sc concentrations into group III‐nitrides, is discussed. High electron mobility transistors, as well as optoelectronic devices, can benefit from this development.